2020
DOI: 10.3892/or.2020.7708
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol synergizes with cisplatin in antineoplastic effects against AGS gastric cancer cells by inducing endoplasmic reticulum stress‑mediated apoptosis and G2/M phase arrest

Abstract: Gastric cancer (GC) is a common gastrointestinal malignancy, and cisplatin (DDP) is an important component of chemotherapeutic regimens for GC. However, the application of DDP is limited by its dose-dependent systemic toxicity. Resveratrol (RES) is a natural polyphenol compound that has chemopreventive and therapeutic effects against various cancers, including GC. However, whether RES can sensitize GC cells to DDP remains unknown. Following RES/DDP combination treatment, cell viability was determined by Cell C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…These data represent a strong motivation to explore the combined effects of RSV with chemotherapeutic agents. As reported in the literature, strong evidence on breast, gastric, and prostate cancer cells, subjected to combined treatment with RSV–DOX or RSV–CIS, has shown a synergistic behavior of RSV towards chemotherapeutic agents [ 61 , 62 , 63 ]. The combined treatments showed variable effects: viability inhibition, apoptosis promotion, epithelial–mesenchymal transition inhibition, intracellular drugs accumulation, and reduction of bone loss due to chemotherapy [ 17 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data represent a strong motivation to explore the combined effects of RSV with chemotherapeutic agents. As reported in the literature, strong evidence on breast, gastric, and prostate cancer cells, subjected to combined treatment with RSV–DOX or RSV–CIS, has shown a synergistic behavior of RSV towards chemotherapeutic agents [ 61 , 62 , 63 ]. The combined treatments showed variable effects: viability inhibition, apoptosis promotion, epithelial–mesenchymal transition inhibition, intracellular drugs accumulation, and reduction of bone loss due to chemotherapy [ 17 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…G1-S or G2-M transitions are regulated by checkpoints that may arrest cell cycle progression in environmental stress conditions. As balanced interactions between cyclins, cyclin-dependent kinases (CDK), and CDK inhibitors (CDI) regulate progression through the cell cycle [ 132 ], altered expression of the cell-cycle-specific proteins by dietary components potentially may sustain the proliferation of neoplastic cells and serve as “effect” biomarkers of their cytotoxic activity. The phenolic compounds of propolis, such as genistein, quercetin, kaempferol, myricetin, luteolin, chrysin, and apigenin, have been confirmed to modulate cell proliferation through an effect on the cell cycle by inducing CDI (p21 and p27) and inhibiting CDK4, CDK2, cyclin D1, and cyclin E [ 133 , 134 , 135 , 136 , 137 , 138 , 139 ].…”
Section: Molecular and Cellular Targets Of Propolis And Its Flavonoid...mentioning
confidence: 99%
“…Many studies have shown that the abnormal fluctuation of the phosphorylation level of eIF2α is associated with the proliferation and invasiveness of tumor cells [ 70 , 71 ]. A combinational treatment of resveratrol and cisplatin can increase the level of phosphorylated eIF2α, which leads to increased intracellular Ca 2+ levels, thereby triggering endoplasmic reticulum stress and apoptosis of gastric cancer cells [ 72 ]. Alongside these treatments, the accumulation of intracellular reactive oxygen species (ROS) has also been shown to be associated with the induction of apoptosis [ 73 ].…”
Section: Overview Of Anti-cancer Properties and Involved Mechanisms O...mentioning
confidence: 99%